DATA OWNERSHIP IN REGULATING BIG DATA IN INDONESIA THROUGH THE PERSPECTIVE OF INTELLECTUAL PROPERTY - Hari Sutra Disemadi (Fakultas Syariah, 2022)
Big data is the process of collecting, analyzing, and utilizing data, which is necessary for the development of many kinds of technologies that are already highly-integrated into the daily lives of many people. The concept of data ownership is often used to be the basis to support the efforts to regulate big data. This point of view argues that data has a number of elements of ownership that needs to be recognized by intellectual property law but does not clearly explain the conceptual connection of data, big data, and intellectual property. Using the normative legal research method, this article found out that the integration of intellectual property elements into the conceptualization of big data regulation could threaten the antitrust or business competition climate in Indonesia. Additionally, the normative space for big data regulations through the intellectual property rights perspective is still too small to be comprehensively described and still needs more concrete evidence from the actual utilization of big data itself. This research aims at providing points of normative reference for future studies on the potentials and risks of regulating big data under the framework of intellectual property law.Big data merupakan proses pengumpulan, analisis dan pemanfaatan data yang berperan penting dalam perkembangan berbagai macam teknologi yang sudah sangat terintegrasi dalam kehidupan masyarakat. Konsep kepemilikan data merupakan konsep yang kerap dijadikan dasar dalam upaya meregulasi big data. Sudut pandang ini berargumen bahwa data memiliki unsur kepemilikan yang harus dihormati oleh hukum kekayaan intelektual, namun tidak secara jelas menjelaskan konseptualisasi antara data, big data, dan kekayaan intelektual. Dengan menggunakan metode penelitian hukum normatif, penelitian ini menemukan adanya pelekatan nilai kekayaan intelektual ke dalam konseptualisasi pengaturan big data, yang mana dapat mengancam iklim persaingan usaha di Indonesia dan secara normatif pengaturan big data melalui hak kekayaan intelektual masih sangat kecil untuk dijabarkan dan membutuhkan bukti yang lebih konkret dari pemanfaatan big data itu sendiri. Penelitian ini bertujuan untuk memberikan rekomendasi secara normatif untuk penelitian di masa mendatang mengenai peluang dan risiko pengaturan big data dalam kerangka hukum kekayaan intelektual.